Protection of apple plants from diseases in the conditions of the Western Forest-steppe - Gunchak, M.; Skorreyko, A. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
Investigated the system of chemical, biological and integrated protection of apple plants from diseases. The effectiveness of the chemical protection system made up — 94—95%. The biological protection system for apples has shown an efficiency of 64.5 to 74%. The system of protection of apple from harmful organisms, which included treatment with both chemical and biological pesticides, showed efficacy from 69 to 97%.